2020
DOI: 10.21203/rs.2.15372/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptability and practicability of self-management for patients with Parkinson's disease based on smartphone applications in China

Abstract: Background China has had about 1.2 billion mobile-phone users, and this number continues to grow. However, mobile-health services (mHealth) are currently in the initial stage, and have not yet prevailed in China. Additionally, the prevalence of Parkinson's disease (PD) in China is 1700/100,000 (≥65 years). Indeed, these PD patients would benefit from mHealth to manage their disease. Therefore, we designed a study to determine attitudes toward smartphone applications (apps) for chronic condition self-management… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The MMAS-8 was used by other investigators beyond the original developers and was shown to be reliable and valid in patients with hypertension (a chronic disease that usually requires concomitant use of medications, as in PD), and valid (linguistic and criterion validity) and responsive in PD patients. Though the eight items of the PRO covers some of the components of MA, and despite having been used in six studies with PD patients, [27][28][29][30][31]54 the MMAS-8 has limited clinimetric data available in the PD population. The MMAS-8 is suitable for screening and correlative studies; however, it cannot be recommended for treatment trials until more evidence regarding reliability and sensitivity to change are available for the PD population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MMAS-8 was used by other investigators beyond the original developers and was shown to be reliable and valid in patients with hypertension (a chronic disease that usually requires concomitant use of medications, as in PD), and valid (linguistic and criterion validity) and responsive in PD patients. Though the eight items of the PRO covers some of the components of MA, and despite having been used in six studies with PD patients, [27][28][29][30][31]54 the MMAS-8 has limited clinimetric data available in the PD population. The MMAS-8 is suitable for screening and correlative studies; however, it cannot be recommended for treatment trials until more evidence regarding reliability and sensitivity to change are available for the PD population.…”
Section: Discussionmentioning
confidence: 99%
“…No scale met the required criteria to be ranked as "Recommended." The Morisky Medication Adherence Scale (MMAS-8), [26][27][28][29][30][31] The Beliefs Related to Medications Adherence questionnaire (BERMA), 32,33 the Beliefs about Medication Questionnaire (BMQ-H), 30,[34][35][36] The Satisfaction with Information on Medicines Scale (SIMS), 37,38 and the Medication Adherence Rating Scale (MARS) 35,39,40 met the criteria of "Suggested;" and the MGL-MAQ, 24,25,34,[41][42][43][44][45][46][47] the Brief Medication Questionnaire (BMQ-S), 23,48,49 the Malaysian Medication Adherence Scale (MALMAS), [50][51][52] and the PD-RX 23 met the criteria of "Listed" (Table 3). The PD-RX 23 it is the only scale developed specifically for the population with PD, but in addition to its clinimetric weakness, it has not been used by any investigator other than the original developers.…”
Section: Criteria Ratingsmentioning
confidence: 99%
See 1 more Smart Citation